TLR5 Supports Development of Placental Labyrinthine Zone in Mice - Yiu, Jensen H. C.; Cheung, Samson W. M.; Cai, Jieling; Chan, Kam-Suen; Chen, Jing; Cheong, Lai Yee; Chau, Hau-Tak; Xu, Aimin; Li, Raymond H. W.; Woo, Connie W. (Frontiers in Cell and Developmental Biology, 2021)
Toll plays an important role in innate immunity and embryonic development in lower-ranked animals, but in mammals, the homolog toll-like receptors (TLR) are reported to facilitate postnatal development of immunity only. Here, we discovered a role of TLR5 in placental development. Tlr5 was highly transcribed during the placenta-forming and functional phases. TLR5 deletion led to a smaller placental labyrinthine zone and lower embryo weight, and the smaller size of embryo was overcorrected, resulting in a higher postnatal body weight. Examination of TLR5-deficient conceptus revealed a decrease in nuclear cAMP-response element-binding protein (CREB), mechanistic target of rapamycin (mTOR) and insulin growth factor-1 receptor (IGF1R) abundances in the placenta-forming phase. Non-flagellin-based TLR5 ligands were detected in serum of female mice and the overexpression of TLR5 alone was sufficient to induce CREB nuclear translocation and mTOR transcriptional activation in trophoblasts. Taken together, we uncovered the participation of TLR5 in the early placental formation in mice, unveiling a role of TLR in embryonic development in higher-ranked animals.